Hypervalent Iodine Compounds as Versatile Reagents for Extremely Efficient and Reversible Patterning of Graphene with Nanoscale Precision - Bao, Lipiao; Zhao, Baolin; Yang, Bowen; Halik, Marcus; Hauke, Frank; Hirsch, Andreas (Advanced Materials, 2021)
Rational patterning and tailoring of graphene relies on the disclosure of suitable reagents for structuring the target functionalities on the 2D-carbon network. Here, a series of hypervalent iodine compounds, namely, 1-chloro-1,2-benziodoxol-3(1H)-one, 1,3-dihydro-1-hydroxy-3,3-dimethyl-1,2-benziodoxole, and 3,3-dimethyl-1-(trifluoromethyl)-1,2-benziodoxole is reported to be extremely efficient for a diversified graphene patterning. The decomposition of these compounds generates highly reactive Cl, OH, and CF3 radicals exclusively in the irradiated areas, which subsequently attach onto the graphene leading to locally controlled chlorination, hydroxylation, and trifluoromethylation, respectively. This is the first realization of a patterned hydroxylation of graphene, and the degrees of functionalization of the patterned chlorination and trifluoromethylation are both unprecedented. The usage of these mild reagents here is reasonably facile compared to the reported methods using hazardous Cl-2 or ICl and allows for sophisticated pattern designs with nanoscale precision, promising for arbitrary nanomanipulation of graphene's properties like hydrophilicity and conductivity by the three distinct functionalities (Cl, OH, and CF3). Moreover, the attachment of functional entities to these highly functionalized graphene nanoarchitectures is fully reversible upon thermal annealing, enabling a full writing/storing/reading/erasing control over the chemical information stored within graphene. This work provides an exciting clue for target 2D functionalization and modulation of graphene by using suitable hypervalent iodine compounds.
CRIS-Team WoS Importer:2021-07-09